Ludological application in the gamification of tertiary level education / Mohamad Izwan Ismail...[et al.] - Ismail, Mohamad Izwan; Abu Bakar, Nur Ain; Mohamed, Mawarni (Universiti Teknologi MARA, Kedah, 2020)
The education system is meant to prepare young minds for the workforce. Yet, despite the rapidly evolving industry, this system is still reminiscent of industrial-age values whereby students are trained to sit in line and follow instructions. On the contrary, the current industry requires candidates who are capable of critical thinking, creativity or flexibility, maintaining motivation, and being engaged with their work. The current conventional education approach lacks the necessary mechanics that drives the development of engagement in students. Through ludology, or game studies and gamification, it becomes possible to modify the current education approach and instill these values in students. Here, we aimed to develop a framework for applying ludological mechanics in the form of gamification to improve student participation and engagement in an education course. The core of the gamification system was developed using Microsoft Excel. The key student participation elements were first identified and segregated into three general categories; in-class participation, lab participation, and participation outside of the classroom. These were then broken down further for a more accurate record of each participation. A points-based reward system was then developed, dubbed “Extra Points” or “ExP” to act as a gamification currency. A shop mechanic was then designed to attribute value to the points. To avoid inflation, a balanced point-based economy was then developed, taking into account student behavior, perceived preferences, as well as feedback. The ExP system effectively assimilates the core values of well-balanced RPGs, encouraging students to willingly and actively participate and engage with the system. In this regard, the ludological approach successfully improves self-motivation in students while enumerating their participation, providing a clear indicator of each students perceived level of engagement during class.